“They Are Worth Their Weight in Gold”: Families and Clinicians’ Perspectives on the Role of First Nations Health Workers in Paediatric Burn Care in Australia - Julieann Coombes; Sarah Fraser; Kate Hunter; Rebecca Ivers; Andrew Holland; Julian Grant; Tamara Mackean (International Journal of Environmental Research and Public Health, 2021)
Burns affect Australia’s First Nations children more than other Australian children, they also experience longer lengths of stay in tertiary burns units and face barriers in accessing burn aftercare treatment. Data sets from two studies were combined whereby 19 families, 11 First Nations Health Worker (FNHW) and 56 multidisciplinary burn team members from across Australia described the actual or perceived role of FNHW in multidisciplinary burn care. Data highlighted similarities between the actual role of FNHW as described by families and as described by FNHW such as enabling cultural safety and advocacy. In contrast, a disconnect between the actual experience of First Nations families and health workers and that as perceived by multidisciplinary burn team members was evident. More work is needed to understand the impact of this disconnect and how to address it.